Method for preparing aluminum-based super-hydrophobic surface through one-step method - ZHANG HAIFENG; CHEN WEIPING; LIU XIAOWEI; TUO YANJING (2018)
The invention provides a method for preparing aluminum-based super-hydrophobic surface through a one-step method and belongs to the technical field of metal surface treatment. The method comprises thefollowing steps: preparing a sodium chloride water solution and a perfluorotetradecanoic acid ethanol solution; after mixing the two solutions, pouring the mixed solution into a hydrothermal reactionkettle; then vertically putting a pure aluminum sheet which is subjected to sand paper grinding and ultrasonic washing into the hydrothermal reaction kettle; after sealing, putting the hydrothermal reaction kettle into a constant-temperature box; after reacting for a period of time, taking out the aluminum sheet; and washing and drying to obtain the aluminum-based super-hydrophobic surface with amicro-nano structure. The method provided by the invention has the advantages of simple preparation and easiness for operation; the requirements on equipment are low, expensive equipment is not needed and experiment conditions